2017
DOI: 10.1080/00071005.2017.1310179
|View full text |Cite
|
Sign up to set email alerts
|

‘Just Google It?’: Pupils’ Perceptions and Experience of Research in the Secondary Classroom

Abstract: While numerous studies examine perceptions of research held by university researchers, studies examining perceptions held by school pupils are rare. To address this gap and following analysis of questionnaire data (N = 2634, KS3/4/5 pupils), we conducted 11 group interviews with 100 pupils in England to investigate their experiences of research during schooling and their perceptions of how research is conceived, conducted and where its utility and significance lie. Thematic analysis of the interview data – inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Most of our medical students are high-achievers, previously attaining high grades by learning and recalling facts. A UK study found that whilst school pupils are generally familiar with the idea of research, for example in forming hypotheses, they have few opportunities to test their own research questions (Yeoman et al, 2017). Whilst considering this evidence, it is also important to note that many of our students in the UK are now graduates, coming from a first degree where they are likely to have been exposed to research experience.…”
mentioning
confidence: 99%
“…Most of our medical students are high-achievers, previously attaining high grades by learning and recalling facts. A UK study found that whilst school pupils are generally familiar with the idea of research, for example in forming hypotheses, they have few opportunities to test their own research questions (Yeoman et al, 2017). Whilst considering this evidence, it is also important to note that many of our students in the UK are now graduates, coming from a first degree where they are likely to have been exposed to research experience.…”
mentioning
confidence: 99%
“…Finally, a number of protracted programmes for secondary and sixth-form students to experience undertaking cutting-edge scientific research have emerged in recent years. These have the potential to address the disconnect between science education and what professional scientists actually do (Braund and Reiss, 2006;Yeoman et al, 2017), which may have a role to play in raising, maintaining or confirming students' aspirations towards STEM subjects (L. . Unfortunately, such programmes are rare globally, with those that do exist often lacking active support from researchers and/or targeting of disadvantaged groups (Bennett et al, 2018;M.O.…”
Section: Deeper Programmesmentioning
confidence: 99%
“…However, exactly how this science is conducted is not often well understood outside of academia, particularly at school-level due to the lack of research methods within current science teaching (e.g. Hodson, 1998;Braund and Reiss, 2006;Yeoman et al, 2017). Currently four projects have been developd for the PRiSE programme at QMUL, which we briefly summarise here indicating key project personnel (referring to the roles mentioned previously).…”
Section: Current Projectsmentioning
confidence: 99%